Watermelon transformation with Zucchini yellow mosaic virus coat protein gene and comparison with parental cultivar - Çürük, Sebahattin; Meşe, Ebru (Pesquisa Agropecuaria Brasileira, 2012)
The objective of this study was to transfer Zucchini yellow mosaic virus coat protein (ZYMV-CP) gene to watermelon cultivar Crimson Sweet (CS) genome, and compare the transgenic T1 and T2 progenies with nontransformed parental cultivar for morphological, pomological, growth and yield characteristics. The ZYMV-CP gene was transferred by Agrobacterium tumefaciens, and the presence of the gene in transgenic T0, T1 and T2 plants was determined by polymerase chain reaction, and the results were confirmed by Southern blot. Two experiments were conducted in two different dates. In both experiments, hypocotyl length of transgenic seedlings was significantly higher than that of nontransgenic parental ones. In the second experiment, the differences between transgenic and nontransgenic individuals were significant concerning fruit rind thickness, flesh firmness, fruit peduncle length, size of pistil scar, fruit strip or flesh color a* values. In conclusion, transferring ZYMV-CP gene to CS genome affected only a few characteristics from 80 traits that have been examined. The changes in rind thickness, flesh firmness and flesh color a* value were favorable while size of pistil scar was undesirable. Together, it may be concluded that transgenic watermelon line having ZYMV-CP gene and parental cultivar CS are very similar.